2002
DOI: 10.1159/000065430
|View full text |Cite
|
Sign up to set email alerts
|

C<i>-fos</i> Antisense Oligodeoxynucleotide Decreases Subcutaneous Bee Venom Injection-Induced Nociceptive Behavior and Fos Expression in the Rat

Abstract: Oligodeoxynucleotide complementary to c-fos mRNA was applied to characterize its effect on the spinal cord Fos expression and relevant nociceptive behaviors challenged by subcutaneous injection of bee venom to the rat hind paw. Nociceptive behavioral responses (spontaneous pain and hyperalgesia) following bee venom (0.2 mg/50 µl) injection were assessed in adult male Sprague-Dawley rats receiving intrathecal administra- tion of c-fos antisense oligodeoxynucleotide (ASO, 50 µg/ 10 µl), sense oligodeoxynucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…Decreased expression of Fos was confirmed by immunofluorescent evidence and was accompanied with decreased allodynia in the early stage. In agreement with our previous study [24], c- fos ASO could inhibit c- fos activation in parallel with the decreased allodynia induced by SNL. The most remarkable inhibitory effect of c- fos ASO on allodynia is at the early stage after SNL, which supports the above concept: c- fos activation contributes more to the induction of allodynia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Decreased expression of Fos was confirmed by immunofluorescent evidence and was accompanied with decreased allodynia in the early stage. In agreement with our previous study [24], c- fos ASO could inhibit c- fos activation in parallel with the decreased allodynia induced by SNL. The most remarkable inhibitory effect of c- fos ASO on allodynia is at the early stage after SNL, which supports the above concept: c- fos activation contributes more to the induction of allodynia.…”
Section: Discussionsupporting
confidence: 93%
“…Fos protein is rapidly expressed in the spinal dorsal horn neurons following noxious peripheral nerve stimulation [21] and correlates well with nociceptive behaviors [19]. Thus, Fos expression is used to identify nociceptive input activated or excited population of neurons [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intrathecal injections of c-Fos AS-ODNs can inhibit Fos protein expression after noxious stimuli [49,50,56-59], their effects on pain behavior are inconsistent. Several studies showed that c-Fos AS-ODNs decrease nociceptive behavior or hyperalgesia following formalin [60], bee venom [59], and adjuvant [58]. On the contrary, Hunter et al and Ibrahim et al reported that c-Fos AS-ODNs increase formalin-induced pain [49,50].…”
Section: The Role Of C-fos and Perk In Central Sensitizationmentioning
confidence: 99%
“…The number of c-Fos-positive neurons began to decline in both superficial layers and deep layers at 4 h and completely disappeared at 96 h after bee venom insult. In comparison with the time course of behavioral nociceptive responses and hyperalgesia induced by bee venom, it is likely that c-Fos expression reflects establishment of a sensitized state at the spinal dorsal horn which requires at least 30 min of persistent primary afferent input to the central site (Wu et al, 2002). The sensitized state of the spinal dorsal horn that may be driven by peripheral nociceptor sensitization is responsible for the development and maintenance of hyperalgesia that disappears with the disappearance of spinal c-Fos expression (Luo et al, 1998; Chen et al, 1999b; Chen and Chen, 2000).…”
Section: Nociceptive and Inflammatory Effects Of Subcutaneous Bee mentioning
confidence: 99%